TINJAUAN HUKUM ISLAM TERHADAP LEGALITAS ABORSI AKIBAT PERKOSAAN DALAM PP NO. 61 TAHUN 2014 - Rohmawati, R. (IAIN Tulungagung, 2015)
The issue of the Government Regulation Number 61/2014 about ReproductionHealth is intended to guarantee the rights of people through the qualityservice. It includes safe and responsible service for mothers to produce highquality generation and reduce the number of mortality of mother. However,such regulation leads to pros and contras because it is considered thatit legalizes abortion. It is clearly stated in the regulation that abortion isallowed due to some conditions such as emergency medical problem or thepregnancy because of rape.Kata kunci: Legalitas Aborsi, Perkosaan, PP No. 61 Tahun 2014, HukumIslam